RANCANG BANGUN ALAT BANTU PENGEPRES MINUMAN KALENG MENGGUNAKAN PNEUMATIK BERBASIS ARDUINO UNO - Rafly, Muhammad; Irtawaty, Andi sri; Ulfah, Maria (Teknik Elektro Politeknik Negeri Balikapapan, 2025)
A drink can is a container made of steel sheet coated with tin. Drink cans are often found in the environment, as well as waste and new conditions. The number of users of these beverage cans can also affect the amount of waste generated. The lack of concern and appreciation from the public for the use of recycled products is also one of the reasons for the unpopularity of recycled products in Indonesia. The problem with can recyclers who collect used beverage cans is that they press the cans by stomping or hitting them so that they can injure the recycler. With this problem introduced a tool that is able to press and reduce the volume of beverage cans automatically without having to be stepped on or hit which is very risky of injuring the recycler. By using the Arduino Uno microcontroller, beverage can presses can be automatic, by simply inserting a drink can into the presser, the proximity sensor will detect the can and pneumatically move the drink can. The cycler can also weigh the pressing results easily because this tool is equipped with an Ultrasonic Sensor sensor to detect whether the container is full or not. The benefits of using a drink can press tool automatically using pneumatics, can lighten the workload on the recycler and can also minimize work accidents on the recycler. The results of this tool can be placed in garbage collectors who really need a tool like this and can also be placed in the environment around the house so that people can immediately recycle drink cans properly and can keep the environment clean.